Features Of Polylingual Education Development In The Republic Of Kazakhstan - Nurgaliyeva, Saniya; Gulnar Muslimanova, Assiya Mashekenova, Zhanat Idrisheva, Madina Yussubaliyeva, (Opción, 2019)
The aim of the study is to investigate features of polylingual education development in the Republic of Kazakhstan via comparative qualitative research methods. As a result, the preparation of English-speaking teachers for secondary, technical and vocational education, higher education has become possible within the framework of the international scholarship of the President of the Republic of Kazakhstan Bolashak. In conclusion, along with the content of university training it is necessary to review the organization of the development of professional and pedagogical competencies of students